2009
DOI: 10.1210/jc.2008-0936
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Thyroxine, Maternal Thyroid Function, and Child Cognition

Abstract: Newborn T4 concentrations within a normal physiological reference range are not associated with maternal thyroid function and do not predict cognitive outcome in a population living in an iodine-sufficient area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 37 publications
6
96
1
1
Order By: Relevance
“…perceptual performance MSCA outcomes (44), consistent with the present findings. By contrast, other authors reported that higher newborn T 4 was unexpectedly associated with lower scores on the visual recognition memory test at the age of 6 months but not with scores for verbal abilities, intelligence or visual motor abilities at the age of 3 years (45). Another study observed no neurological impairment in infants aged !1 year born to mothers with elevated TSH during pregnancy (46).…”
Section: Discussionmentioning
confidence: 85%
“…perceptual performance MSCA outcomes (44), consistent with the present findings. By contrast, other authors reported that higher newborn T 4 was unexpectedly associated with lower scores on the visual recognition memory test at the age of 6 months but not with scores for verbal abilities, intelligence or visual motor abilities at the age of 3 years (45). Another study observed no neurological impairment in infants aged !1 year born to mothers with elevated TSH during pregnancy (46).…”
Section: Discussionmentioning
confidence: 85%
“…By contrast, one study did not find any relationship between maternal T4 levels and cognitive development in children at 6 months (visual recognition memory) and 3 years of age (PPVT and Wide Range of Visual Motor Ability). However, this study included only a very small number of women with abnormal thyroid function (Oken et al, 2009). Berbel et al (2009 carried out a trial in Spain that showed better gross and fine motor coordination and socialization (Brunet-Lezine Scale) in 18-month-old children whose mothers were supplemented with iodine from early pregnancy, compared to those who took the supplement from late pregnancy.…”
Section: Iodinementioning
confidence: 99%
“…A growing body of evidence indicates that developmental delay even occurs in children whose mothers had thyroxine (T 4 ) levels that were slightly lower (but still within the normal range) early in pregnancy (4,5,6,7,8), although some studies were negative (9,10). However, participants in these studies were followed until the age of 3 using developmental tests like the Bayley Scales of Infant Development (version II), which have a poor prognostic value for future cognitive impairments (11,12).…”
Section: Introductionmentioning
confidence: 99%